Low phosphorus induces differential metabolic responses in eucalyptus species improving nutrient use efficiency - Silva, Franklin Magnum de Oliveira; Bulgarelli, Rafaela Gageti; Mubeen, Umarah; Caldana, Camila; Andrade, Sara Adrian L.; Mazzafera, Paulo (Frontiers in Plant Science, 2022)
Phosphorus (P) is a vital nutrient for plant growth. P availability is generally low in soils, and plant responses to low P availability need to be better understood. In a previous study, we studied the growth and physiological responses of 24 species to low P availability in the soil and verified of eucalypts, five (Eucalyptus acmenoides, E. grandis, E. globulus, E. tereticornis and Corymbia maculate) contrasted regarding their efficiency and responsiveness to soil P availability. Here, we obtained the metabolomic and lipidomic profile of leaves, stems, and roots from these species growing under low (4.5 mg dm-3) and sufficient (10.8 mg dm-3) P in the soil. Disregarding the level of P in the soils, P allocation was always higher in the stems. However, when grown in the P-sufficient soil, the stems steadily were the largest compartment of the total plant P. Under low P, the relative contents of primary metabolites, such as amino acids, TCA cycle intermediates, organic acids and carbohydrates, changed differently depending on the species. Additionally, phosphorylated metabolites showed enhanced turnover or reductions. While photosynthetic efficiencies were not related to higher biomass production, A/Ci curves showed that reduced P availability increased the eucalypt species' Vcmax, Jmax and photosynthetic P-use efficiency. Plants of E. acmenoides increased galactolipids and sulfolipids in leaves more than other eucalypt species, suggesting that lipid remodelling can be a strategy to cope with the P shortage in this species. Our findings offer insights to understand genotypic efficiency among eucalypt species to accommodate primary metabolism under low soil P availability and eventually be used as biochemical markers for breeding programs.